Structure and geographical distribution of spiders (Aranei) of Daghestan Republic - G. M. Abdurahmanov; S. V. Aliyeva (Юг России: экология, развитие)
There are the results of studying fauna and geographical spreading of the spiders of Dagestan. Now the fauna of spiders consists of 25 families, 103 genius and 200 species, from which 98 species are noted for Dagestan for the first time, and 2 species are described as new for the science. (Drassodes dagestanus sp.n. и Drassodes archibensis sp.n. [5].)